An Analysis on Writing Anxiety of Indonesian EFL College Learners - Wahyuni, Sri; Umam, M. Khotibul (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2017)
This study aims at analyzing the writing anxiety of English students of an Islamic State College in East Java, Indonesia. This study described the levels, dominant type, and main factors of writing anxiety of the English students. Fifty English students at the fourth semester participated in this study. Two closed-ended questionnaires, Second Language Writing Anxiety Inventory (SLWAI) proposed by Cheng, and Causes of Writing Anxiety Inventory (CWAI) proposed by Rezaei and Jafari were employed to collect the data. The findings revealed that 54% of the students experienced high level of writing anxiety, 44% experienced moderate level of writing anxiety, and 2% experienced low level of writing anxiety. The dominant type of writing anxiety was cognitive writing anxiety, which is based on the highest mean among two other types of writing anxiety. Then there are four main factors that cause writing anxiety. They are linguistic difficulties, fear of teachers’ negative comments, insufficient writing practice, and time pressure.